The interspecific competition of tropical estuarine macrophytes is not density-dependent - Nunes, Laís Samira Correia [UNESP]; Camargo, Antonio Fernando Monteiro [UNESP] (Elsevier, 2020)
The interspecific competition of aquatic macrophytes may be density-dependent and its outcome has importance for the monospecific and mixed stands zonation in tropical estuaries. To evaluate the growth of Spartina alterniflora and Crinum americanum and the effect of the initial densities on their competition we developed a laboratory experiment using five planting densities of young individuals (8:0, 5:3, 4:4, 3:5 and 0:8) and two sediment types (lower and middle estuary sediment: salinity 20.90 and 6.60, respectively). We tested the hypotheses that (i) in the lower estuary sediment S. alterniflora would have greater competitive ability than C. americanum even at lower initial densities, because of its great salt tolerance; (ii) However, at the middle estuary sediment the competitive outcome would depend on initial plant densities, because of the favorable brackish conditions for both species. Our results corroborated our first hypothesis, since in the lower estuary sediment S. alterniflora limited the C. americanum aboveground biomass by asymmetrical competition regardless of their planting densities. However, our second hypothesis was not confirmed as S. alterniflora had greater competitive ability and limited C. americanum at any planting density in the middle estuary sediment. We conclude that the competition between S. alterniflora and C. americanum in the two sediment types is not density-dependent. We suggest that in the lower estuary S. alterniflora might have competitively excluded C. americanum regardless of their colonization densities; and that in the middle estuary the arrival order might be important to the mixed stands organization.
Keywords: Colonization; Competitive exclusion; Crinum americanum; Planting density; Propagules pressure; Salinity gradient; Spartina alterniflora